HUBUNGAN ANTARA TINGKAT KONSENTRASI SISWA DENGAN KETEPATAN FREE THROW DALAM PERMAINAN BOLA BASKET (STUDI PADA PESERTA EKSTRAKURIKULER BOLA BASKET SMA NEGERI 1 SOOKO MOJOKERTO TAHUN AJARAN 2013/2014) - ALIM KURNIAWAN, NORIS (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Concentration is one of the most important mental activity especially in sport. By concentrating in each of movements and activities within the sports, the players will be able to run the game well since they're focusing their mind and body in to one thing. Concentration is needed in sports activity like shooting, throwing and hitting. Shooting is one of the important techniques in basketball, while free throw is one of the shooting techniques in basketball. Although free throw is seen to be easy to be done, but it is relatively difficult since it need a good technique and mental condition. This study aims to find out the relation between the students concentration level towards the accuracy of freethrow and also to find out how big the influence of a concentration in free-throwing for the students in Basketball extracurricular in SMA Negeri 1 Sooko Mojokerto. This research is a non-experimental research and using a descriptive and quantitative approach with correlational design. The subject of the research are 33 students of basketball extracurricular in SMA Negeri 1 Sooko. The Samples were taken by using a purposive sampling from the population of a whole students. The research is using an grid concentration test and foul shoot instrument. Based on the result of data analysis, it is shown that the value of r(counts) is bigger than r(table) (0.402>0.344) which means that there is a correlation or a significant relation between the concentration level towards the accuracy of basketball free throw. The value of a correlation of the concentration towards free throw is 16,14%. Keywords : Concentration, Free throw Basketball